Strengthen the connections - Shin, Eul-Yong; Son, Hae Jung (NATURE PUBLISHING GROUP, 2024)
Achieving good electrical contact without damaging underlying layers is critical to the performance of photovoltaic modules. Research now reports a silver electrode embedded into a polymer matrix and a silver/chromium protection layer, enabling over 14%-efficient flexible organic photovoltaic modules with improved stability under illumination.